Experiences from tsunami relief activity: implications for medical training - Manni Balasubramaniam, Sudharsanam; Roy, Gautam; Mohan, Yogesh (Canadian Medical Education Journal, 2012)
A tsunami struck the coast of Tamilnadu and Pondicherry on 26 December 2004. Jawaharlal Institute of Postgraduate Medical Education & Research, (JIPMER) in Pondicherry played a vital role in providing medical relief. The experiences from the relief activities revealed areas of deficiency in medical education in regards to disaster preparedness. A qualitative study using focus group discussion was employed to find the lacunae in skills in managing medical relief measures. Many skills were identified; the most important of which was addressing the psychological impact of the tsunami on the victims. Limited coordination and leadership skills were also identified. It is recommended that activity-based learning can be included in the curriculum to improve these skills.